2010
DOI: 10.1002/cne.22477
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of the bilateral brainstem projections from the whisker and forepaw regions in rat primary motor cortex

Abstract: The whisker region in rat primary motor (MI) cortex projects to several brainstem regions, but the relative strength of these projections has not been characterized. We recently quantified the MI projections to bilateral targets in the forebrain , and the present study extends those findings by quantifying the MI projections to bilateral targets in the brainstem. We found that both the whisker and forepaw regions in MI project most strongly to the basal pons and superior colliculus. While the MI forepaw region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 62 publications
6
33
0
Order By: Relevance
“…Cerebellar projection cells respond to vibrissa input (Bosman et al, 2010) and cerebellar output can affect the timing in vM1 cortex (Lang et al, 2006), but again there is no composite understanding. The situation is more advanced for the case of the superior colliculus, which receives direct vibrissa input via a trigeminotectal pathway (Killackey and Erzurumlu, 1981; Figure 3), indirect input via a corticotectal pathway through vS1 and vM1 cortices (Alloway et al, 2010; Miyashita et al, 1994; Wise and Jones, 1977) and can drive whisking as well (Hemelt and Keller, 2008). Recording in awake free ranging animals show that cells in the colliculus respond to vibrissa touch (Cohen and Castro-Alamancos, 2010), while experiments that used fictive whisking with anesthetized animals show that cells can respond to movement in the absence of contact (Bezdudnaya and Castro-Alamancos, 2011).…”
Section: Next Stepsmentioning
confidence: 99%
“…Cerebellar projection cells respond to vibrissa input (Bosman et al, 2010) and cerebellar output can affect the timing in vM1 cortex (Lang et al, 2006), but again there is no composite understanding. The situation is more advanced for the case of the superior colliculus, which receives direct vibrissa input via a trigeminotectal pathway (Killackey and Erzurumlu, 1981; Figure 3), indirect input via a corticotectal pathway through vS1 and vM1 cortices (Alloway et al, 2010; Miyashita et al, 1994; Wise and Jones, 1977) and can drive whisking as well (Hemelt and Keller, 2008). Recording in awake free ranging animals show that cells in the colliculus respond to vibrissa touch (Cohen and Castro-Alamancos, 2010), while experiments that used fictive whisking with anesthetized animals show that cells can respond to movement in the absence of contact (Bezdudnaya and Castro-Alamancos, 2011).…”
Section: Next Stepsmentioning
confidence: 99%
“…This suggests that SI processing of deep somatic input may preferentially influence information processing in APT. The APT was also shown to receive input from the MI forepaw and whisker areas (O'Donoghue et al, 1987;Miyashita et al, 1994;Alloway et al, 2010). However, these MI projections terminate more dorsally in APT.…”
Section: Dsz Projections To the Midbrainmentioning
confidence: 92%
“…Descending projections from MI were also shown to terminate in RN (Gwyn and Flumerfelt, 1974;Giuffrida, 1991;Miyashita et al, 1994;Alloway et al, 2010). The RN, through its connections with the cerebellum, inferior olive, and spinal cord (Gwyn, 1971;Murray and Gurule, 1979;Huisman et al, 1983;Swenson and Castro, 1983;Kennedy, 1990), participates in locomotive coordination of the shoulder and upper limbs and also in skilled movement of the forelimbs (Lawrence and Kuypers, 1968;Gibson et al, 1985;Whishaw et al, 1998;Muir and Whishaw, 2000).…”
Section: Dsz Projections To the Midbrainmentioning
confidence: 95%
“…Different divisions of 7N receive substantial and differential input, primarily from nuclei of the midbrain, pons, and medulla (Erzurumlu and Killackey, 1979;Hinrichsen and Watson, 1983;Travers and Norgren, 1983;Isokawa-Akesson and Komisaruk, 1987;Mogoseanu et al, 1994;Fay and Norgren, 1997b;Pinganaud et al, 1999;Grinevich et al, 2005;Alloway et al, 2010). A direct projection from the motor cortex to motoneurons innervating the vibrissae is also evident (Grinevich et al, 2005).…”
Section: Afferent Projectionsmentioning
confidence: 98%
“…However, studies with more conventional tracers concluded that, quantitatively, the superior colliculus provided the most direct pathway between the vibrassal motor cortex and vibrissae motoneurons (Alloway et al, 2010). The contralateral red nucleus further provides a relay for cortical and cerebellar input to 7N, and electrical stimulation of the red nucleus produced movement of both the vibrissae and eyelid (Hinrichsen and Watson, 1983;Isokawa-Akesson and Komisaruk, 1987;Hattox et al, 2002).…”
Section: Midbrain Projectionsmentioning
confidence: 98%